Population Pharmacokinetics and Exposure–Response Analysis of a Fixed‐Dose Combination of Ivermectin and Albendazole in Children, Adolescents, and Adults - Algorta, Jaime (2024)
Trichuris trichiura is a soil-transmitted helminth causing intestinal disease. Albendazole is the standard treatment despite its moderate efficacy, which is improved when co-administered with ivermectin. A fixeddose combination adds practical advantages mainly for mass drug administration. The aim of this article is to define the population pharmacokinetic models and exposure–response of an innovative albendazole/ivermectin combination. Data were obtained from a phase I clinical trial in healthy adults and from a phase II trial in children and adolescents infected with T.trichiura. Nonlinear mixed-effects models were built for albendazole and ivermectin using NONMEM®. Area under the curve was calculated using the empirical Bayes estimates of the pharmacokinetic parameters of each individual and used for evaluation of exposure–response between cure rate and pharmacokinetic exposure. The pharmacokinetics of albendazole was described using a two-compartmental model with first-order absorption and the pharmacokinetics of ivermectin was described using a twocompartmental model with zero-order followed by first-order absorption. Clearance and volume of distribution increased with body weight for both albendazole and ivermectin. Day 1 area under the curve of albendazole and ivermectin from the children and adolescents treated with the combination regimens were similar to the healthy adults treated with control drugs. A flat exposure–response relationship was observed between the cure rate and drug exposure. Population pharmacokinetic of a combination of albendazole and ivermectin in children, adolescents, and adults, either healthy or infected by T.trichiura was described. The dosage selected in the phase II trial was appropriate for the subsequent phase III.